2000
DOI: 10.2741/gomes
|View full text |Cite
|
Sign up to set email alerts
|

The development of auditory attention in children

Abstract: In this paper we review the development of four components of auditory attention: arousal, orienting, selective attention and sustained attention. We focus especially on the processes responsible for the selection of specific stimuli for further processing because these are essential for learning and development. Although much work still needs to be done, there is evidence of developmental change in some of the components of attention, especially early in infancy. Later developmental improvements seem to be pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
42
0
10

Year Published

2006
2006
2016
2016

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 109 publications
(55 citation statements)
references
References 91 publications
3
42
0
10
Order By: Relevance
“…Therefore, it appears that the attention-benefit ratio reflects the ability or willingness to follow the attention instructions, not the ability to remember items in the lists. One must note that this pattern of results does not imply that young children cannot control attention; indeed, other literature suggests that they can do so to some extent (e.g., Gomes et al, 2000;Lane & Pearson, 1982). The result suggests only that making use of selective attention for mnemonic purposes demanded a level of control that was generally beyond what most of the children-and many of the adults-could manage.…”
Section: Correlations and Regressionsmentioning
confidence: 85%
“…Therefore, it appears that the attention-benefit ratio reflects the ability or willingness to follow the attention instructions, not the ability to remember items in the lists. One must note that this pattern of results does not imply that young children cannot control attention; indeed, other literature suggests that they can do so to some extent (e.g., Gomes et al, 2000;Lane & Pearson, 1982). The result suggests only that making use of selective attention for mnemonic purposes demanded a level of control that was generally beyond what most of the children-and many of the adults-could manage.…”
Section: Correlations and Regressionsmentioning
confidence: 85%
“…Third, it is possible that infants have stable representations of intensity and that they can separate the overlapping components of sound coming from different sources, but that they are unable to selectively attend to one sound while ignoring another (Gomes, Molholm, Christodoulou, Ritter, & Cowan, 2000). Bargones and Werner (1994) found that while adults expecting to hear a low-intensity tone at one frequency did not hear tones at other unexpected frequencies, infants detected expected and unexpected frequencies equally well.…”
Section: Increasing Specificitymentioning
confidence: 99%
“…The N1 is mostly sensitive to sound audibility and salience and parallels behavioral sound detection thresholds (Martin et al, 1997). Based on its known functional significance in adults as well as late emergence and specific elicitation conditions in children (long inter-stimulus intervals, ISI), we have suggested (Èeponienë et al, 2002; Èeponienë et al, 2005) that, at least partially, the N1 emerges as a complementing and balancing mechanism to the development of focused and sustained attention (Gomes et al, 2000;Coch et al, 2005b;Wible et al, 2005). That is, the auditory N1 may reflect a "gate-keeping" mechanism for sensory information, which depends on the load and direction of the ongoing mental activity.…”
Section: Introductionmentioning
confidence: 99%